(untitled) (Journal on Geoinformatics, Nepal, 2020)
The existing classical geodetic datum of Nepal called as Nepal Datum was developed and realized almost 40 years ago through the concerted surveying involving astronomic measurements by Czechoslovakian team along with Doppler observations and Trigonometric Surveying by British team. Since the realization of this geodetic datum by establishment of First Order Control Network at 68 locations, secular and co-seismic crustal movements has potentially disturbed the integrity of the network. Any survey activities based on use of existing datum without proper understanding and discretion can potentially compromise the outputs of surveying. On another hand, the classical datum is not directly compatible with the current surveying trends based on GNSS technologies. In order to ensure access to precise and GNSS compatible datum, there is an urgent need to develop geocentric datum. . In this article, we examine and recommend ways to realize geocentric datum by maximal utilization of already existent and necessary components for a functional geocentric datum. This paper is divided into three sections: Ingredients, Recipe and the Cooking. The ingredients section discusses the infrastructure for geocentric datum, the recipe section discusses the procedures to defining geocentric datum and the Cooking section discusses on the part of capacity development.